N-demethylsinomenine metabolite and its prototype sinomenine activate mast cells via MRGPRX2 and aggravate anaphylaxis - Qin, Youfa; Huang, Yihan; Ji, Xiaolan; Gong, Ling; Luo, Shiqiong; Gao, Jiapan; Liu, Rui; Zhang, Tao (Frontiers in Pharmacology, 2024)
Sinomenine hydrochloride (SH) is commonly used in the treatment of rheumatoid arthritis. It activates mast cells and induces anaphylaxis in the clinical setting. Adverse drug reactions can be caused by activation of MAS-associated G protein-coupled receptor X2 (MRGPRX2) on mast cells. Because the ligand binding site of MRGPRX2 is easily contacted in dilute solvents, it can be activated by many opioid drug structures. N-Demethylsinomenine (M-3) has a similar chemical structure to that of the opioid scaffold and is a major metabolite of SH. We sought to clarify whether M-3 induces anaphylaxis synergistically with its prototype in a mouse model. Molecular docking computer simulations suggested a similar binding effect between M-3 and SH. M-3 was chemically synthesized and analyzed by surface plasmon resonance to reveal its affinity for MRGPRX2. Temperature monitoring, in vivo hindlimb swelling and exudation test, and in vitro mast cell degranulation test were used to explore the mechanism of MRGPrx2 mediated allergic reaction triggered by M-3. Reduced M-3-induced inflammation was evident in MrgprB2 (the ortholog of MRGPRX2) conditional (Cpa3-Cre/MrgprB2flox) knockout (MrgprB2-CKO) mice. Additionally, LAD2 human mast cells with MRGPRX2 knockdown showed reduced degranulation. M-3 activated LAD2 cells synergistically with SH as regulated by GRK2 signaling and IP3R/PLC/PKC/P38 molecular signaling pathways. The results indicate that the M-3 metabolite can activate mast cells synergistically with its prototype SH via MRGPRX2 and aggravate anaphylaxis. These findings provide important insights into drug safety.